Răspunsuri

2014-08-16T10:51:07+03:00
A)4√5 -2√5 +7√5= 11√5 -2√5 = (11-2)*√5=  9√5

b)5√7 -9√7 +4√7= 9√7 -9√7= (9-9)√7=  0*√7=0

c)1,5√11 -14√7 +0,5√11 -6√7= (1,5+0,5) * √11 -(14+6)*√7= 2√5 -20√7= 2(√5 -10√7)

d)0,(4)= 4/9

1/3 √5 -3/4√5 +2/3 -4/9 +1/12 √5  aducem la acelasi numitor

12√5 -27√5 + 24 -16 + 3√5= 15√5 -27√5 +24-16= 3√5(5-9) + 8= 3√5 * (-4) +8=

= 4[3√5 * (-2) +2]= 4 ( -6√5 +2= -24√5 +8
2014-08-16T13:46:20+03:00
a) 4√5 -2√5 +7√5= 11√5 -2√5 = (11-2)*√5=  9√5

b )5√7 -9√7 +4√7= 9√7 -9√7= (9-9)√7=  0*√7=0

Tot ce ai facut ai copiat de la primu!!Si restu.Frate ,nu m-ai scrieti daca nu stiti.